Basaloid squamous cell carcinoma of the sinonasal tract with metastasis to the liver: A case report and literature review - Toe, B.P.; Ramli, Norlisah; Lam, S.Y.; Wong, Kum Thong; Prepageran, Narayanan (SAGE Publications, 2015)
Basaloid squamous cell carcinoma (BSCC) is a rare subtype of squamous cell carcinoma. To date, only 95 cases of sinonasal BSCC have been reported in the English-language literature, and they account for 5% of all cases of head and neck BSCC. We describe what we believe is only the second reported case of a sinonasal tract BSCC that metastasized to the liver. The patient was a 36-year-old woman who presented with right-sided nasal obstruction and a foul-smelling discharge. Clinical examination and imaging identified a large lobulated enhancing mass in the right nasal cavity. Following excision of the mass, the patient was scheduled for radiotherapy. However, before it could be administered, follow-up imaging detected a metastasis to the liver and lung, and the patient was switched to chemotherapy. Initially, she responded well clinically, but at 5 months postoperatively, a follow-up CT showed an increasing metastatic presence in the liver and bone. The patient died of her disease 1 year after surgery.